Studies on Some 3-Oxo-5-benzylidene-6-methyl-(4H) -2-substitutedpyridazines with Antinociceptive and Antiinflammatory Activities - (:unkn) unknown (My University, 2003)
In this study, some new 3-oxo-5-benzylidene-6-methyl-(4H)-2-substituted pyridazine derivatives have been prepared by the reaction of 5-substituted benzylidene-6-methyl-(4H)-pyridazin-3-one with several substituted benzoyl-methyl bromides. The structures of the compounds have been elucidated by IR, 1H-NMR and elemental analysis. Antinociceptive (only for compound IIIa) and anti-inflammatory activity studies were evaluated by using in vivo tests. The anti-inflammatory activity was studied by means of the "carrageenan paw edema", whereas the "acetic acid writhing" test was used to assess the antinociceptive activity. Qualitatively, compound IIIa was shown to exert anti-inflammatory effect as potent as phenylbutazone and antinociceptive effect similar to acetylsalicylic acid.
Keywords: 3-Oxo-5-benzylidene-6-methyl-(4H)-2-substituted pyridazines; Anti-inflammatory activity; Antinociceptive activity; Synthesis